Anticancer activity of repurposed hemostatic agent desmopressin on AVPR2‑expressing human osteosarcoma - Sobol, Natasha Tatiana (2021)
Osteosarcoma is the most prevalent primary bone malignancy. Due to its high aggressiveness, novel treatment strategies are urgently required to improve survival of patients with osteosarcoma, especially those with advanced disease. Desmopressin (dDAVP) is a widely used blood-saving agent that has been repurposed as an adjuvant agent for cancer management due to its antiangiogenic and antimetastatic properties. dDAVP acts as a selective agonist of the vasopressin membrane receptor type 2 (AVPR2) present in the microvascular endothelium and in some cancer cells, including breast, lung, colorectal and neuroendocrine tumor cells. Despite the fact that dDAVP has demonstrated its antitumor efficacy in a wide variety of tumor types, exploration of its potential anti-osteosarcoma activity has, to the best of our knowledge, not yet been conducted. Therefore, the aim of the present study was to evaluate the preclinical antitumor activity of dDAVP in osteosarcoma. Human MG-63 and U-2 OS osteosarcoma cell lines were used to assess in vitro and in vivo therapeutic effects of dDAVP. At low micromolar concentrations, dDAVP reduced AVPR2-expressing MG-63 cell growth in a concentration-dependent manner. In contrast, dDAVP exhibited no direct cytostatic effect on AVPR2-negative U-2 OS cells. As it would be expected for canonical AVPR2-activation, dDAVP raised intracellular cAMP levels in osteosarcoma cells, and coincubation with phosphodiesterase-inhibitor rolipram indicated synergistic antiproliferative activity. Cytostatic effects were associated with increased apoptosis, reduced mitotic index and impairment of osteosarcoma cell chemotaxis, as evaluated by TUNEL-labeling, mitotic body count in DAPI-stained cultures and Transwell migration assays. Intravenous administration of dDAVP (12 µg/kg; three times per week) to athymic mice bearing rapidly growing MG-63 xenografts, was indicated to be capable of reducing tumor progression after a 4-week treatment. No major alterations in animal weight, biochemical or hematological parameters were associated with dDAVP treatment, confirming its good tolerability and safety. Finally, AVPR2 expression was detected by immunohistochemistry in 66% of all evaluated chemotherapy-naive human conventional osteosarcoma biopsies. Taking these findings into account, repurposed agent dDAVP may represent an interesting therapeutic tool for the management of osteosarcoma. Further preclinical exploration of dDAVP activity on orthotopic or metastatic osteosarcoma models are required.